HOTAIR gene polymorphisms contribute to increased neuroblastoma susceptibility in Chinese children. Issue 12 (30th March 2018) - Yang, Xu; He, Jing; Chang, Yitian; Luo, Annie; Luo, Ailing; Zhang, Jiao; Zhang, Ruizhong; Xia, Huimin; Xu, Ling
Abstract : BACKGROUND: Neuroblastoma is the most frequently diagnosed extracranial solid tumor in children. Previous studies have shown that single‐nucleotide polymorphisms in some genes are associated with the risk of multiple cancers, including neuroblastoma. Although Hox transcript antisense intergenic RNA ( HOTAIR ) gene polymorphisms have been investigated in a variety of cancers, to the authors' knowledge the relationships between HOTAIR gene polymorphisms and neuroblastoma susceptibility have not been reported to date. The objective of the current study was to evaluate the correlation between HOTAIR gene polymorphisms and neuroblastoma risk in Chinese children. METHODS: The authors genotyped 6 polymorphisms (rs920778 A>G, rs12826786 C>T, rs4759314 A>G, rs7958904 G>C, rs874945 C>T, and rs1899663 C>A) of the HOTAIR gene in 2 Chinese populations including 393 neuroblastoma cases and 812 healthy controls. The strength of the associations was evaluated using odds ratios and 95% confidence intervals. Further stratification analyses were conducted to explore the association between the HOTAIR gene polymorphisms rs12826786 C>T, rs874945 C>T, and rs1899663 C>A with neuroblastoma susceptibility in terms of age, sex, clinical stage of disease, and sites of origin. RESULTS: The authors found that the rs12826786 C>T ( P =.013), rs874945 C>T ( P =.020), and rs1899663 C>A ( P =.029) polymorphisms were significantly associated with increased neuroblastoma risk. In stratification analyses, these associations were more predominant in females and among patients with tumor in the retroperitoneal region or mediastinum. The remaining 3 polymorphisms were not found to be related to neuroblastoma susceptibility. CONCLUSIONS: The results of the current study verified that HOTAIR gene polymorphisms are associated with increased neuroblastoma risk and suggest that HOTAIR gene polymorphisms might be a potential biomarker for neuroblastoma susceptibility. Cancer 2018;124:2599‐606 . © 2018 American Cancer Society . Abstract : Hox transcript antisense intergenic RNA ( HOTAIR ) gene polymorphisms are associated with an increased risk of neuroblastoma. In the current study, these associations are more predominant in females and in patients with tumor in the retroperitoneal region or mediastinum.